Penggunaan Gambaran Penggunaan Antibiotik pada Pasien Sepsis Dewasa di RSUD X Jakarta: Antibiotik pada Pasien Sepsis - Pasaribu, Donna Mesina Rosadini; William, William; Siceria, Putri Denova (Jurnal MedScientiae, 2026)
Sepsis is a collection of symptoms that occur as a result of an overreaction of the human immune response caused by microbes. Sepsis can progress to septic shock and if it persists accompanied by decreased immunity can cause death. Antibiotic therapy should be given as soon as the diagnosis, starting with empiric antibiotics which are then adjusted according to clinical response or culture results. This study aims to describe the use of antibiotics in RSUD X Jakarta, in adult sepsis cases. The research method is descriptive observational with consecutive sampling in accordance with the inclusion and exclusion criteria. Data collection was obtained through medical records of patients diagnosed with sepsis. The results showed that the most patients sepsis were aged less than 60 years, there were 51%, men 53%, the length of stay was less than 10 days, 62% and 55% patients had no comorbidities. The focus of infection was mostly in the lungs 38%, patients who sampled the most monotherapy antibiotics were Ceftriaxone 51.1%, the most combination use was Levofloxacin and Meropenem 21.1%, and the longest duration of antibiotic use less than 7 days with Ceftriaxone 43 (53.75%). There were 64 people (64%) of these sepsis patients died. The study concluded that the focus of infection in sepsis patients was mostly in the lungs, men aged less than 60 years, without any comorbid disease, length of stay less than 10 days. The choice of antibiotic monotherapy for septic patients, given Ceftriaxone, for combination therapy given Levofloxacin and Meropenem antibiotics.